Diagnostic Laparoscopy as a Gold Standard Investigation in Sub-Fertility (Journal of Fatima Jinnah Medical University, 2018)
Objective: Diagnostic Laproscopy as a Gold standard investigation in patients with sub-fertility. Study Design: Retrospective descriptive study. Place and duration: Health Care Centre (Pvt.) Ltd. Peshawar from 2nd May 2012-15th August 2012. Material and Methods: We reviewed case records of all the patients who underwent diagnostic laparoscopy for their sub-fertility. Data was collected from patients case records between 2 May 2012 to 15 August 2012 in department of obstetrics and gynaecology Health Care Centre (Pvt.) Ltd. Peshawar. Results: 132 cases were reviewed out of which 32.92% had primary sub-fertility and 22.08% had secondary sub-fertility. The mean age of the patients in the primary sub-fertility group was 21.6years and 33.3years in the secondary sub-fertility group. Majority of our patients in the primary sub-fertility group had weight gain of 6.6% and hirsutism was seen in 5.42% followed by irregular cycles in 5.0% of the patients. No symptoms were observed in 12.08% patients, so probably the primary sub-fertility group had polycystic ovarian disease syndrome. However the number of patients with hirsutism was 6.25% in the secondary sub-fertility group as well. In the secondary sub-fertility group 4.17% of patients had weight gain, and irregular cycles were seen in 4.58% of the patients. Some of the patients approximately 4.58% had no complaints. The duration of the problem in the primary sub-fertility group was more seen between 2-5years duration. 29 patients 12.08% were in this time period and more than 5years duration was noticed in 48 patients 20%. The duration of the problem in secondary sub-fertility group for more than 5 years was noted in 32 patients 13.3%. We did a hysterosalpingogram in about 27% of our patients as a diagnostic tool for tubal patency. However in 7.92% of patients hysterosalpingogram could not be performed due to technical difficulties. Post operative pain was the first complaint observed in 10.42% of the patients followed by backache in 5.82%. However 12.08% had no complaints in the primary infertility group. In the secondary sub-fertility group pain was observed in 7.08% followed by backache in 4.58% of patients. No complaints were observed in 3.75% of patients. In our study four cases of genital tuberculosis were diagnosed and one case was complicated with peritionitis due to rupture of transverse colon and proceeded to laprotomoy. Conclusion: Laparoscopy is a gold standard tool for females presenting with sub-fertility. The benefits of laparoscopy are that there is less pain, minimal scars, less hospital stay with early recovery and less resources consumed. It is also a better modality of investigation or a better diagnostic tool in the hands of skilled operator. However it is a skilled procedure which requires expertise of a trained surgeon.
Keywords: Sub-fertility. Laparoscopy. Primary Sub-fertility. Secondary Sub-fertility. Tubal Patency.